ABDOMINAL SEPSIS : problems that need to be addressed - Hamdamov, B.Z.; Hotamov, I.E.; Hamdamov, A.B. (JOURNAL OF EDUCATION AND SCIENTIFIC MEDICINE, 2024)
This review scientific article presents current information on the etiology, pathogenesis, diagnosis, clinical manifestation and treatment of abdominal sepsis. Common etiologies of abdominal sepsis in developed countries include appendicular process perforation, cholecystitis, perforated gastrointestinal cancer, and diverticulitis. Peritonitis is one of the leading causes of abdominal sepsis. Despite the fact that there are many studies on peritonitis, in general, this problem is still global, since peritonitis can provoke the development of abdominal sepsis.